2020
DOI: 10.1180/clm.2020.8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation kinetics of sepiolite

Abstract: The kinetic parameters of the thermal degradation of sepiolite were evaluated with a new method based on thermal analysis data. Thermogravimetric/differential thermal analysis curves were recorded for the natural and preheated sepiolite samples in the temperature range 25–800°C for 4 h. The temperature-dependent height of the exothermic heat flow peak for the thermal decomposition of sepiolite located at ~850°C on the differential thermal analysis curve was taken as a kinetic variable for the thermal degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The difference is attributed to the low thermal stability of photoelectric dyes, hydrolysis of amide bonds, and diffusion in PBS. It was reported that the activation energy in the Arrhenius equation becomes large at higher temperatures [34]. In other words, the thermal degradation of a material accelerates nonlinearly as temperature increases.…”
Section: Accelerated Aging Durability Test Using Pbs At 60°cmentioning
confidence: 98%
“…The difference is attributed to the low thermal stability of photoelectric dyes, hydrolysis of amide bonds, and diffusion in PBS. It was reported that the activation energy in the Arrhenius equation becomes large at higher temperatures [34]. In other words, the thermal degradation of a material accelerates nonlinearly as temperature increases.…”
Section: Accelerated Aging Durability Test Using Pbs At 60°cmentioning
confidence: 98%
“…Consequently, while the coating lacking the bio-based pigment experiences a slight color shift when exposed to high temperatures, the sepiolite-based additive successfully preserves consistent color. This phenomenon is ascribed to the well-known thermal durability of sepiolite [84,85]. Sepiolite effectively shields the indigo extract, with which it is infused, from potential thermal degradation phenomena.…”
Section: Outdoor Resistancementioning
confidence: 99%
“…By mimicking the lithification processes and using the hardening mechanisms of cement and concrete, a cemented sepiolite aggregate was obtained from natural sepiolite clay under hydrothermal treatment with calcium aluminium silicate hydrate (C-A-S-H) or Al-tobermorite formation, and because of the low temperature (≤473.15 K) of hydrothermal solidification, the microstructure (porosity) of raw sepiolite might be preserved in the matrix of the sepiolite specimens (Sarıkaya et al , 2020). The hydrothermal technology has been applied widely not only in inorganic material synthesis, but also in organic material compositions (Lyu et al , 2014; He et al , 2019).…”
mentioning
confidence: 99%